Neuromuscular and perceptual fatigue in English male handball players during international competition - Moss, S.; McWhannell, N.; Twist, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Elite handball tournaments require players to compete on successive days with limited recovery time between matches. This scheduling can result in player fatigue, which may have potential consequences on match performance. Therefore, the purpose of this study was to investigate the demands imposed on England squad players competing in the U19 European Open Championships, and the subsequent impact of competition on neuromuscular and perceptual fatigue. Methods: Fourteen handball players (age 17.1 ± 0.73 years) competing for England agreed to participate. The tournament consisted of eight matches played over five days, with players competing in two matches on days one, three, and four, and one match on days two and five. Player loading was quantified through measurement of heart rate (HR) during matches and session rating of perceived exertion (sRPE), taken 30 minutes after each match. Neuromuscular function was measured using a maximal 10 m sprint performed after matches one, five, and eight and flight time during a counter-movement jump (CMJ), performed immediately before and after each match. Subjective measures of fatigue, sleep quality, general muscle soreness, stress and mood were monitored daily using a 1 (negative) to 5 (positive) likert scale. Individual component scores were also totalled to give an overall rating of player well-being. Results: Average playing time, sRPE and HR during matches was 20:20 ± 4:19 min, 148.3 ± 41.6 AU and 86 ± 3% of maximal HR, respectively. Sprint time over 10 m increased during the tournament (P < 0.001), with values of 1.84 ± 0.7 s, 1.89 ± 0.6 s, and 1.98 ± 0.12 s, on day one, five and eight, respectively. Similarly, there was a trend for a decrease in CMJ flight time during the tournament (P = 0.06). Overall well-being decreased during the tournament (P = 0.008), with values of 20.08 ± 1.98, 18.17 ± 1.53, 18.17 ± 1.03, 17.83 ± 1.7 at baseline, day two, four and five, respectively. Analysis of individual components revealed increased fatigue on day four compared to baseline (P = 0.04), and increased muscle soreness, which was different to baseline on days two, three, four and five (P = 0.001), as well as between day three and day five (P = 0.03). Discussion: The physiological loading and limited recovery time between matches during an international tournament caused progressive decrements in neuromuscular performance and well-being in English handball players. This information should be used to identify how players fatigue during competition, as well as providing important information for coaches on effective interchange strategies to optimize individual and team performance.